Centrifuge separation effect on bacterial indicator reduction in dairy manure. (15th April 2017) - Liu, Zong; Carroll, Zachary S.; Long, Sharon C.; Roa-Espinosa, Aicardo; Runge, Troy
Abstract: Centrifugation is a commonly applied separation method for manure processing on large farms to separate solids and nutrients. Pathogen reduction is also an important consideration for managing manure. Appropriate treatment reduces risks from pathogen exposure when manure is used as soil amendments or the processed liquid stream is recycled to flush the barn. This study investigated the effects of centrifugation and polymer addition on bacterial indicator removal from the liquid fraction of manure slurries. Farm samples were taken from a manure centrifuge processing system. There were negligible changes of quantified pathogen indicator concentrations in the low-solids centrate compared to the influent slurry. To study if possible improvements could be made to the system, lab scale experiments were performed investigating a range of g-forces and flocculating polymer addition. The results demonstrated that polymer addition had a negligible effect on the indicator bacteria levels when centrifuged at high g forces. However, the higher g force centrifugation was capable of reducing bacterial indicator levels up to two-log10 in the liquid stream of the manure, although at speeds higher than typical centrifuge operations currently used for manure processing applications. This study suggests manure centrifuge equipment could be redesigned to provide pathogen reduction to meet emerging issues, such as zoonotic pathogen control. Highlights: Farm scale centrifuge is not effective for bacteria reduction. High speed and long retention time centrifuge is effective for bacteria reduction. Adding PAM increases solid and bacteria reduction rates without centrifuge.